PERAN KEPOLISIAN DALAM PENANGGULANGAN TINDAK PIDANA MENYALAHGUNAKAN PENGANGKUTAN DAN/ATAU NIAGA BAHAN BAKAR MINYAK YANG DISUBSIDI PEMERINTAH BERDASARKAN UNDANG-UNDANG NOMOR 22 TAHUN 2001 TENTANG MINYAK DAN GAS BUMI DI KEPOLISIAN DAERAH RIAU - Zulkifli '; Erdianto '; Mexsasai Indra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Indonesia has a wealth of natural resources that abound. Fertile soil surface and in it also contained a variety of mineral in the form of minerals, ores, various chemical elements and various stones including precious stones that can be processed for the welfare of the people, especially oil and gas. Realized oil and gas is the livelihood of many people, the Indonesian government since the first has been working to protect the natural resources of this country. This can be seen with the UU No. 32 of 2009 on the Protection and Environmental Management, which is a systematic and integrated upayah done to preserve the function of the environment and prevent pollution and / or damage to the environment that includes the planning, utilization, control , maintenance, supervision, and enforcement. And UU No. 22 of 2001 on Oil and Natural Gas regulations governing the business activities of oil and natural gas also includes legal sanctions, whether it be administrative sanctions, civil and criminal sanctions. The publishing of criminal sanctions in the UU on Oil and Gas, which is contained in Article 51 to Article 56 can be said that the Indonesian government seriously ensure the enforcement of the law on Oil and Gas.Oil – Adminisrative - Control